ANALIZA FLUXURILOR DE NUMERAR ȘI A CONCORDANȚEI ACESTORA CU REZULTATELE FINANCIARE - Nirean, Elena (CEP USM, 2024)
The research results refer to the assessment of the evolution of cash flows and their consistency with the financial results of the entity in order to evaluate efficiency and develop financial policies to optimize cash flows within the analyzed entity. A significant gap between the net cash flow and the obtained financial result was observed in the entity, primarily caused by changes in current assets that led to the withdrawal of cash. In the same direction, the repayment of loans, reduction of current liabilities, payment of dividends, and income tax expenses acted, under whose influence the total gap increased. The negative influence of these factors was partially mitigated as a result of receipts in the form of loans and profit. The positive action of these and other factors influenced the reduction of the gap between the financial result and the net cash flow. At the same time, this did not allow the company to fully compensate for the deviation of the net flow from the obtained financial result.
ANALYSIS OF CASH FLOWS AND THEIR CONSISTENCY WITH FINANCIAL RESULTS
Keywords: assets; gap; cash flow; net flow; financial results; active; decalaj; flux de numerar; flux net; rezultate financiare